Free piston linear generator for low grid power generation - Abdalla, I. (EDP Sciences, 2017)
Generating power is of great importance nowadays across the world. However, recently, the world became aware of the climatic changes due to the greenhouse effect caused by CO2 emissions and began seeking solutions to reduce the negative impact on the environment. Besides, the exhaustion of fossil fuels and their environmental impact, make it is crucial to develop clean energy sources, and efforts are focused on developing and improving the efficiency of all energy consuming systems. The tubular permanent magnet linear generators (TPMLGs) are the best candidate for energy converters. Despite being suffering problem of attraction force between permanent magnets and stator teeth, to eliminate such attraction force, ironless-stator could be considered. Thus, they could waive the presence of any magnetic attraction between the moving and stator part. This paper presents the design and analysis of ironless -cored TPMLG for low grid power generation. The main advantages of this generator are the low cogging force and high efficiency. Therefore, the magnetic field computation of the proposed generator has been performed by applying a magnetic vector potential and utilizing a 2-D finite element analysis (FEA). Moreover, the experimental results for the current profile, pressure profile and velocity profile have been presented. © The authors, published by EDP Sciences, 2017.